1986
DOI: 10.3109/01485018608986925
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Integrity of Human Sperm in the Presence ofUreaplasma Urealyticum

Abstract: Several species of Mycoplasmu have been isolated from the human genital tract, the most common being M. hominis and Ureuplasmu ureulyfk-um. A causal relationship between such infections and sperm dysfunction and infertility has yet to be established. It was the purpose of this study to examine the effects of U. urealyticum infection on the function of sperm as assessed by seminal fluid analysis (SFA), in vitro penetration of bovine cervical mucus (BCMP), and the hamster sperm penetration assay (SPA). No signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Similarly, studies have reported no adverse effects of Ureaplasma-infected spermatozoa on in vivo semen variables (5,10,11), whereas others have reported a significantly lower sperm concentration (12,13) and significantly reduced sperm motility (13) in Ureaplasma-infected semen samples.…”
mentioning
confidence: 93%
“…Similarly, studies have reported no adverse effects of Ureaplasma-infected spermatozoa on in vivo semen variables (5,10,11), whereas others have reported a significantly lower sperm concentration (12,13) and significantly reduced sperm motility (13) in Ureaplasma-infected semen samples.…”
mentioning
confidence: 93%
“…Apart from these evidences, no other studies have reported effects from U. urealyticum infection on sperm parameters. U. urealyticum infection had no effect on sperm function as observed during sperm analysis, in vitro bovine cervical mucus penetration assay and Hamster’s oocyte sperm penetration assay (Shalhoub et al. , 1986).…”
Section: Effects Of Microorganismsmentioning
confidence: 96%